A Review Article on “Organ-on-a-Chip Platforms: A Novel Approach for Disease Modeling and Drug Discovery” - Mohammed shariq,; Zeenath fatima,; Asna sabahath,; Veeragoni jayadev, (Asian Journal of Pharmaceutical Research and Development, 2026)
ABSTRACT: An innovative method that addresses the drawbacks of conventional two-dimensional (2D) cell cultures and animal models in biomedical research is organ-on-a-chip (OoC) technology. The intricate microenvironment of human tissues cannot be replicated by conventional methods, and using animals for research is expensive, time-consuming, and unethical. OoC devices, sometimes referred to as microphysiological systems, mimic physiological circumstances such fluid flow, mechanical stresses, and biochemical gradients by combining microfluidics with three-dimensional (3D) tissue engineering. The biocompatibility, transparency, and affordability of polydimethylsiloxane (PDMS) make it a common manufacturing material. High-throughput drug testing, quick analysis, and improved tissue microenvironment representation are some benefits of OoC systems. Their promise in drug screening and illness modeling is demonstrated by applications such as kidney-on-a-chip and heart-on-a-chip. Notwithstanding obstacles such surface effects and fluid mixing restrictions, OoC technology offers a viable, moral, and effective substitute for developing individualized medication and enhancing the results of scientific research.